SEJARAH PERTUMBUHAN DAN PERKEMBANGAN BAHASA ARAB - Layla Hasibuan; Tasya Hasibuan (Jurnal Sathar, 2023)
Arabic is one branch of the many Semitic languages ​​that developed tens or even thousands of years ago. Arabic is a language that has many speakers and this language also has its own characteristics that make it different from other languages ​​in general. The development of the Arabic language had such a big influence that it became a language and was established as an international language. Arabic has also experienced various phases starting from the growth phase, development until now. This article aims to describe and explain the history of the growth and development of the Arabic language from the beginning of its growth to its development until now.